2011
DOI: 10.3892/ol.2011.299
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin synergizes with low-dose oxaliplatin in the HCT116 colon cancer cell line by inducing enhanced apoptosis

Abstract: Abstract. The present study aimed to examine the combined effects of oxaliplatin (L-OHP) and rapamycin (RAPA) in the HCT116 colon cancer cell line. The growth inhibitory effect was evaluated by MTT assay as a monotherapy or combination therapy. IC 50 values were determined using CalcuSyn 2.0 software. To determine the interaction of the drugs, the combination index (CI) was calculated using the Chou-Talalay method. Apoptosis was investigated using flow cytometry and Western blotting. Acridine orange staining w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Ru-1 induced the arrest of CT26 and HCT116 cells in the G2/M phase, and Ru-2 caused G2/M phase arrest in SW480 cells, which is likely related to the molecular changes in the cancer cells ( Figure 7 ). Investigation of the effects of different treatment regimens on the apoptosis of CT26 and HCT116 cells demonstrated that oxaliplatin treatment appears to exhibit moderate effects on cell apoptosis, which is consistent with our research [ 26 , 34 , 35 ]. There are no in vitro alternative methods or their combinations which could fully replace in vivo methods for acute systemic toxicity [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…Ru-1 induced the arrest of CT26 and HCT116 cells in the G2/M phase, and Ru-2 caused G2/M phase arrest in SW480 cells, which is likely related to the molecular changes in the cancer cells ( Figure 7 ). Investigation of the effects of different treatment regimens on the apoptosis of CT26 and HCT116 cells demonstrated that oxaliplatin treatment appears to exhibit moderate effects on cell apoptosis, which is consistent with our research [ 26 , 34 , 35 ]. There are no in vitro alternative methods or their combinations which could fully replace in vivo methods for acute systemic toxicity [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…The patients who have a high p‐mTOR expression in liver metastases had poor prognoses after curative resection in the current study, indicating that those patients are likely candidates for chemotherapy and the mTOR pathway could be a pharmacological therapeutic target. Our data showed that the inhibition of p‐mTOR by rapamycin decreased the cellular proliferation of colorectal cancer cells in vitro, as reported previously 33 . However, everolimus monotherapy, a rapamycin analog, did not cause an objective tumor response for refractory colorectal cancer patients in a clinical study 28 .…”
Section: Discussionsupporting
confidence: 88%
“…While metronomic oxaliplatin has not been widely explored thus far in pancreatic cancer, it has been shown to enhance overall cytotoxic effect in combination with chemotherapeutics in other GI cancers. 44,45 Oxaliplatin was found to significantly decrease VEGF levels in breast and gastric cancer cell lines when treated at two logarithmic dose levels below IC 50 . 46 In addition, when administered as part of a quadruplet regimen of nab-paclitaxel, leucovorin and bevacizumab, a refracted low oxaliplatin dose of 50 mg/m 2 was found to be tolerable with 25% of patients reporting grade 3 and higher neuropathy while displaying good clinical activity.…”
Section: Discussionmentioning
confidence: 99%
“…While metronomic oxaliplatin has not been widely explored thus far in pancreatic cancer, it has been shown to enhance overall cytotoxic effect in combination with chemotherapeutics in other GI cancers 44,45 . Oxaliplatin was found to significantly decrease VEGF levels in breast and gastric cancer cell lines when treated at two logarithmic dose levels below IC 50 46 .…”
Section: Discussionmentioning
confidence: 99%